Externally driven plasmaspheric ULF waves observed by the Van Allen Probes. Issue 1 (30th January 2015) - Takahashi, Kazue; Denton, Richard E.; Kurth, William; Kletzing, Craig; Wygant, John; Bonnell, John; Dai, Lei; Min, Kyungguk; Smith, Charles W.; MacDowall, Robert
Abstract We analyze data acquired by the Van Allen Probes on 8 November 2012, during a period of extended low geomagnetic activity, to gain new insight into plasmaspheric ultralow frequency (ULF) waves. The waves exhibited strong spectral power in the 5–40 mHz band and included multiharmonic toroidal waves visible up to the eleventh harmonic, unprecedented in the plasmasphere. During this wave activity, the interplanetary magnetic field cone angle was small, suggesting that the waves were driven by broadband compressional ULF waves originating in the foreshock region. This source mechanism is supported by the tailward propagation of the compressional magnetic field perturbations at a phase velocity of a few hundred kilometers per second that is determined by the cross‐phase analysis of data from the two spacecraft. We also find that the coherence and phase delay of the azimuthal components of the magnetic field from the two spacecraft strongly depend on the radial separation of the spacecraft and attribute this feature to field line resonance effects. Finally, using the observed toroidal wave frequencies, we estimate the plasma mass density for L = 2.6–5.8. By comparing the mass density with the electron number density that is estimated from the spectrum of plasma waves, we infer that the plasma was dominated by H+ ions and was distributed uniformly along the magnetic field lines. The electron density is higher than the prediction of saturated plasmasphere models, and this "super saturated" plasmasphere and the uniform ion distribution are consistent with the low geomagnetic activity that prevailed.